Reutilization of chemical waste in methodologies for analyses of neutral detergent fiber and acid detergent fiber - Lourenço, Maria do Socorro Nahuz; Berchielli, Telma Teresinha [UNESP]; Sader, Ana Paula de Oliveira [UNESP]; Malheiros, Euclides Braga [UNESP]; Messana, Juliana Duarte [UNESP]; Canesin, Roberta Carrilho [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
The disposal of chemical waste and the precision of analyses of the neutral (NDF) and acid (ADF) detergent fiber contents were evaluated utilizing conventional (Van Soest) and alternative methods of analyses. The recovery of acetone promoted both economic and environmental gains, with a recovery rate of 84.12%. The precision of the analyses was not observed in most of the determinations with reutilization of chemical waste in all the analytical methods tested, in spite of promoting decrease in cost, time invested in the preparation of solutions and the disposal of chemical waste.

Foram avaliados descarte de resíduos químicos em análises dos teores de fibra em detergente neutro (FDN) e fibra em detergente ácido (FDA), utilizando métodos convencional (Van Soest) e alternativos de análises. A recuperação da acetona promoveu ganhos tanto econômico como ambiental, observando-se taxa de recuperação de 84,12%. A precisão das análises não foi observada na maioria das determinações com reutilização de resíduos químicos, em todos os métodos analíticos testados, apesar de promover redução no custo, no tempo investido no preparo das soluções e no descarte de resíduos químicos.
Reutilização de resíduos químicos em metodologias para análises de fibra em detergente neutro e fibra em detergente ácido
Keywords: animal nutrition; chemical analysis; Sustainability; Nutrição animal; Sustentabilidade; análise química